CARICOM : unity in adversity - Hall, Kenneth O. (UWI-CARICOM Project GeorgetownGY, 2000)
Highlights the reasons for the survival of the Caribbean Community. Focuses on the factors which enable it to emerge from the crises of the '70s and '80s. Considers whether it can come to terms with the challenges of the 21st century and gainfully utilise the opportunity inherent in the new dispensation the 21st century has spawned.